Identidad corporal para la prevención del abuso sexual infantil en los niños de preparatoria de la escuela de educación básica Julio María Matovelle de la ciudad de Loja, periodo académico 2018-2019. - Armijos Camacho, Karla Tatiana (2020)
Child sexual abuse is a current issue, daily news reports make known unpleasant situations of violation and abuse of children's rights, UNICEF mentions that 4 out of 10 children are sexual victims by family members and people close to the family, motivated by this situation and considering that this problem should be treated with responsibility, I have proposed to investigate the topic: BODY IDENTITY FOR THE PREVENTION OF CHILD SEXUAL ABUSE IN THE CHILDREN OF THE BASIC EDUCATION JULIO MARIA MATOVELLE HIGH SCHOOL OF THE CITY OF LOJA, ACADEMIC PERIOD 2018- 2019, whose general objective is to expand knowledge about body identity for the prevention of child sexual abuse, the literary review addressed issues related to body identity and prevention of child sexual abuse, the methods that have been used are: scientific, inductive, deductive, analytical, synthetic and descriptive statistics; To get information, the instrument applied surveys parents was the questionnaire of knowledge of sexual abuse and prevention skills based on Tutty (1992). The population chosen for research was 22 children, the results allowed to determine that a They have 72.72% in knowledge and 63.64% of sexual prevention skills, which corresponds to a medium level. After the application of the proposal they obtained 90.90% of knowledge and 86.36% in skills of sexual prevention which corresponds to a high level, since it is very satisfactory when obtaining positive results, concluding the educational strategy “! My treasure, my little body, I take care of it because it is beautiful!” That increased the knowledge of sexual abuse and developed prevention skills, it is recommended to apply the proposal to work on the prevention of child sexual abuse.